2008
DOI: 10.5424/sjar/2008064-349
|View full text |Cite
|
Sign up to set email alerts
|

Intrabreed variability and relationships for 41 carcass and meat traits in Pirenaica cattle

Abstract: A total of 125 13-month-old, entire males of the Pirenaica breed were selected from among the progeny of nine different sires. They were used to study the intrabreed variability of 41 carcass and meat traits, including weights, lengths, diameters and perimeters, grading parameters, dissection of the sixth rib, pH, colour and meat texture variables, and sensory attributes. Pearson correlations were also calculated. Coefficients of variation ranged from 3.5% for dressing percentage to 47.0% for fat red index, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
7
0
3
Order By: Relevance
“…Wulf et al (1997) found that there was a significant (P < 0.05) positive correlation between a* value and panel tenderness as well as b* value and panel tenderness; however, a* and b* values were not related to juiciness or flavor. Panea et al (2008), on the other hand, found a positive correlation between a* value and sensory taste panel juiciness (0.36). Although the current results had no significant phenotypic correlations between a*, b*, and juiciness, significant positive phenotypic correlations were detected (P < 0.05) between a* and b* values and flavor intensity and overall mouthfeel.…”
Section: Resultsmentioning
confidence: 96%
“…Wulf et al (1997) found that there was a significant (P < 0.05) positive correlation between a* value and panel tenderness as well as b* value and panel tenderness; however, a* and b* values were not related to juiciness or flavor. Panea et al (2008), on the other hand, found a positive correlation between a* value and sensory taste panel juiciness (0.36). Although the current results had no significant phenotypic correlations between a*, b*, and juiciness, significant positive phenotypic correlations were detected (P < 0.05) between a* and b* values and flavor intensity and overall mouthfeel.…”
Section: Resultsmentioning
confidence: 96%
“…On average, standard error of pH values reported in the present paper was lower than those reported some other authors (Renand et al ., ; Maher et al ., ) but are similar to those for animals raised and slaughtered under controlled conditions (Chambaz et al ., ; Serra et al ., ). Intra‐breed variability is of interest for breeders who are seeking a recognisable brand, as they have to offer a homogeneous product to the market (Panea et al ., ). Regarding the relation between pH and colour, a negative correlation was found between both pH 24 and pH 10 with colour traits at 48 h and 10 days (Table ), with pH 10 having higher coefficients of correlation than pH 24 .…”
Section: Resultsmentioning
confidence: 97%
“…Intra-breed variability was, in general, similar to those reported by Chambaz et al (2003) (SE = 0.4, in average) or Serra et al (2004) (SE = 0.4, in average). Panea et al (2008) reported that the L* of the muscle of Pirenaica was less variable than a* or b*, and muscle b* had a coefficient of variation that was nearly twice that of a*. Breed affected all colour traits (Table 3).…”
Section: Colour Variables: Principal Component Analysis Means and CLmentioning
confidence: 99%
“…El pH 24 fue de 5,5 que se encuentra en el rango normal para la especie y permite descartar efectos sobre el resto de las variables estudiadas (Panea, 2002;Monsón et al, 2004;Panea et al, 2008a;Panea et al, 2010).…”
Section: Resultsunclassified
“…Los valores para las pérdidas por cocinado coinciden con los descritos por otros autores en las mismas razas Martínez-Cerezo et al, 2001;Panea et al, 2008a;Barahona et al, 2016).…”
Section: Pérdidas Por Cocinadounclassified